Implementation of a renal pharmacist consultant service — Information sharing in paper versus digital form. (20th February 2021) - Seiberth, Sarah; Bauer, Dominik; Schönermarck, Ulf; Mannell, Hanna; Stief, Christian; Hasford, Joerg; Strobach, Dorothea
Abstract: What is known and objective: Renal impairment (RI) and renal drug‐related problems (rDRP) often remain unrecognized in the community setting. A "renal pharmacist consultant service" (RPCS) at hospital admission can support patient safety by detecting rDRP. However, the efficient information sharing from pharmacists to physicians is still discussed. The aim of the study was to test the implementation of a RPCS and its effectiveness on prescription changes and to evaluate two ways of written information sharing with physicians. Methods: Urological patients with eGFRnon‐indexed of 15‐59 ml/min and ≥1 drug were reviewed for manifest and potential rDRP at admission by a pharmacist. Written recommendations for dose or drug adaptation were forwarded to physicians comparing two routes: July‐September 2017 paper form in handwritten chart; November 2017‐January 2018 digital PDF document in the electronic patient information system and e‐mail alert. Prescription changes regarding manifest rDRP were evaluated and compared with a previous retrospective study without RPCS. Results and discussion: The RPCS detected rDRP in 63 of 234 (26.9%) patients and prepared written recommendations (median 1 rDRP (1‐5) per patient) concerning 110 of 538 (20.5%) drugs at admission. For manifest rDRP, acceptance rates of recommendations were 62.5% (paper) vs 42.9% (digital) ( P = 0.16). Compared with the retrospective study without RPCS (prescription changes in 21/76 rDRP; 27.6%), correct prescribing concerning manifest rDRP significantly increased by 27.1%. What is new and conclusion: A RPCS identifies patients at risk for rDRP and significantly increases appropriate prescribing by physicians. In our hospital (no electronic order entry, electronic chart or ward pharmacists), consultations in paper form seem to be superior to a digital PDF document. Abstract : By implementing a "renal pharmacist consultant service" (RPCS), that included screening medication for renal drug related problems (rDRP) in patients with renal impairment and forwarding this information as written consultation to physicians on ward, significantly higher prescription changes regarding manifest rDRP were made than in a six months retrospective phase without RPCS. Hence, the service improved in‐patient medication safety. By testing two different ways of information sharing on urological wards with paper charts, consultations as yellow paper inlay, whereby the information was directly available at the point of prescription, seemed to be superior to digital information sharing as PDF document in the electronic patient information system.